Knowledge and experience of students concerning the professional masters in nursing - Claudia Mara de Melo Tavares; Maria Madalena Januário Leite (Rev Rene, 2014)
The objective of the study is to analyze the knowledge and experience of students concerning the Professional Masters in Nursing. We interviewed 12 students admitted to the masters in 2010, through focus groups. The study was conducted from 2010 to 2012.We used the content analysis, obtaining the following result: The masters holds great relationship with the practice aimed at transformation; it contributes significantly to the development of critical skills training, despite the existing social prejudice and the product of the masters aims at contributing directly to the service. We conclude that in nursing there is a fertile ground for the development of Professional Masters, its expansion is necessary and should consider the political project of the profession, which presupposes the formation of a critical nurse and endowed with strong social commitment.